Passividade na interface prótese/pilar intermediário de infraestrutura implantossuportadas confeccionadas pela tecnologia CAD/CAM e método convencional - Araújo, Gabriela Monteiro de (2014)
The objective of this research was to evaluate the passivity and strain induced in infrastructures screwed on abutments, made by CAD/CAM technology, and to compare these samples with parts manufactured by conventional casting. Using CAD/CAM technology, 4 samples were made from zirconia (Zircad) and 4 samples were manufactured from cobaltchrome (CoCrcad). The control groups were 4 specimens of cobalt-chrome, made by onepiece casting (CoCrci), for a total of 12 infrastructures. To evaluate the passivity, the infraestructures were installed on the abutments. One end was tightened and the vertical gap between the infrastructure and the prosthetic abutment was measured with scanning electron microscopy (250×). The mean strain in these infrastructures was analyzed via the photoelasticity test. A significant difference (p = 0.000) in passivity was observed between the control (CoCrci) and sample groups (CoCrcad and CoCrci). CoCrcad exhibited the best value of passivity (48.76 ± 13.45 μm) and CoCrci the worst (187.55 ± 103.63 μm), Zircad presented an intermediate value (103.81 ± 43.15 μm). When compared to the other groups, CoCrci showed the highest mean strain around the implants (17.19 ± 7.22 kPa). It was concluded that the zirconia infrastructure made by CAD / CAM showed a higher vertical marginal misfit than those made in cobalt-chromium alloy with the same methodology, however, the tension generated in the implants was similar. The CAD/CAM technology is more accurate for passivity and mean strain of infrastructure screwed on abutments than conventional manufacturing techniques